Program Mentoring Khusus UKM Kota Tangerang Sebagai Langkah Pemulihan Ekonomi Mitra Terdampak Pandemi Covid-19 - Marista Sutadipraja; Ghina Kemala Dewi; Iwan Setiadi (Jurnal Pengabdian Kepada Masyarakat (JPKM) Langit Biru, 2023)
The Covid-19 pandemic has had an impact on various aspects of Indonesian people's lives. The MSME sector experienced a significant decline in revenue as a result of reduced demand and movement restrictions. One of the government programs in the recovery of the MSME sector is to provide capital assistance to the Productive Micro Business Entities of Presidential Assistance (BPUM) in the form of Direct Cash Assistance (BLT). In addition to the economic assistance provided by the Government, MSMEs require comprehensive training and special assistance in running a business in the next phase in order to be able to face the challenges of running a business during the Pandemic. These community service partners are representatives of 6 sub-district SMEs affected by the Covid-19 pandemic who received BLT in Tangerang City. The Special Assistance Program activities that have been implemented have received a good response from the target audience. The results felt by partner SMEs who participated in the special mentoring program were an increase in sales revenue during the mentoring period for Cemil Tangerang SMEs by 71%, Muezzea SME petshop by 62%, and Al Hijab by 36%. The decline in the income of Clean Washing SMEs for shoe and helmet washing services was 40%, this was because during the Covid 19 pandemic, people prioritized primary needs over secondary needs. The provision of capital stimulus assistance for SMEs has not been accompanied by the right marketing strategy as a form of investment for business actors.